Whole‐genome sequencing identifies missense mutation in GRM6 as the likely cause of congenital stationary night blindness in a Tennessee Walking Horse. (3rd August 2020) - Hack, Yael L.; Crabtree, Elizabeth E.; Avila, Felipe; Sutton, Roger B.; Grahn, Robert; Oh, Annie; Gilger, Brian; Bellone, Rebecca R.
Abstract: Background: The only known genetic cause of congenital stationary night blindness (CSNB) in horses is a 1378 bp insertion in TRPM1 . However, an affected Tennessee Walking Horse was found to have no copies of this variant. Objectives: To identify the genetic cause for CSNB in an affected Tennessee Walking Horse. Study design: Case report detailing a whole‐genome sequencing (WGS) approach to identify a causal variant. Methods: A complete ophthalmic exam, including an electroretinogram (ERG), was performed on suspected CSNB‐affected horse. WGS data were generated from the case and compared with data from seven other breeds (n = 29). One hundred candidate genes were evaluated for coding variants homozygous in the case and absent in all other horses. Protein modelling was used to assess the functional effects of the identified variant. A random cohort of 90 unrelated Tennessee Walking Horses and 273 horses from additional breeds were screened to estimate allele frequency of the GRM6 variant. Results: ERG results were consistent with CSNB. WGS analysis identified a missense mutation in metabotropic glutamate receptor 6 ( GRM6 ) (c.533C>T p.Thr178Met). This single nucleotide polymorphism (SNP) is predicted to be deleterious and protein modelling supports impaired binding of the neurotransmitter glutamate. This variant was not detected in 273 horses from three additional breeds. The estimated allele frequency in Tennessee Walking Horses is 10%. Main limitations: Limited phenotype information for controls and no additional cases with which to replicate this finding. Conclusions: We identified a likely causal recessive missense variant in GRM6 . Based on protein modelling, this variant alters GRM6 binding, and thus signalling from the retinal rod cell to the ON‐bipolar cell, impairing vision in low light conditions. Given the 10% population allele frequency, it is likely that additional affected horses exist in this breed and further work is needed to identify and examine these animals.